Credibility of online political news among Egyptian youth - ElAbd, Dalia (AUC Knowledge Fountain, 2012)
This study confirms previous literature discoveries that perceived credibility of medium, source and message have a direct influence on the perceived credibility of online political news. Each credibility factor is examined separately to identify its influence and strength on the dependent variable. Medium credibility, Internet, is considered the factor that has the strongest influence on perceived credibility of online political news, followed by the source then finally message of online political news. Consumption of online political news has also a direct influence on perception of credibility of online political news but to a much lesser extent. Timely coverage, freedom of speech and dynamic representation are Internet’s inherent features and are highly recognized by Egyptian youth as credibility factors. As for other credibility factors related to believability, objectivity and balance youth become more skeptical about credibility of online political news. Many reasons led to this doubtful view but the most apparent reason in this study is attributed to the abuse of Internet as a communication tool for online political news and lack of regulation. Hence, the uncontrollable freedom of publishing and commenting on political news stories by average citizens who could be politically ignorant, with personal agendas and without any media knowledge.